1156 A Pediatric Case of UNC80 Mutation and Abnormal Respiratory Control Treated with Positive Airway Pressure Therapy. (27th April 2018) - Hong, H; Kretzmer, R; Kato, R; Ward, S D
Abstract: Introduction: Mutations in the UNC80 gene, which encodes a large protein highly expressed in the brain and cerebellum and is necessary for the appropriate function of a sodium leak channel NALCN, can cause a channelopathy.1, 2 In humans it has been described to cause a phenotype of hypotonia, growth retardation and congenital encephalopathy.3 In animal models deficiency of functional NALCN leads to disrupted respiratory patterns with apnea followed by bursts of breathing.4 To our knowledge, there has been no published description of sleep-disordered-breathing in humans with UNC80 mutations. Report of Case: We describe an 8 year-old male with a pathogenic UNC80 mutation, intellectual disability, epilepsy, and a gastrostomy-tube who was admitted for pneumonia, and per mother's history had an irregular respiratory pattern for years. He was observed to have respiratory "pauses" during sleep, intermittent desaturations recorded to 80s on continuous pulse oximetry, and periodic breathing during wakefulness. He had chronic hypoventilation on morning capillary blood gases with respiratory acidosis and compensatory metabolic alkalosis with a PCO2 of 55mmHg and serum bicarbonate of 34 mEq/L. Polysomnography (PSG) done 5 years prior to our evaluation had revealed a severely elevated central sleep apnea index (117.8 events/hour), but mother had declined admission for work up at that time and supplemental oxygen was ordered by his pediatrician. Previous brain imaging was normal. Bi-level positive airway pressure (BPAP) therapy was initiated and well-tolerated which rapidly corrected his CO2 to normal range. A follow-up split-night PSG revealed persistent central apnea (213.5 events/hour), which improved with BPAP titration. He tolerated therapy well with increased daytime alertness. Conclusion: Pediatric patients with UNC80 gene mutations may have an abnormal respiratory rhythm with severe central apnea, periodic breathing and hypercapnia during sleep and wakefulness, mirroring findings in animal models, and they may require assisted ventilation.